Antimicrobial effect of commercial phage preparation Stafal® on biofilm and planktonic forms of methicillin-resistant Staphylococcus aureus - Dvořáčková, Milada; Růžička, Filip; Benešík, Martin; Pantůček, Roman; Dvořáková-Heroldová, Monika (Folia microbiologica, 2019)
Staphylococcus aureus may be a highly virulent human pathogen, especially when it is able to form a biofilm, and it is resistant to antibiotic. Infections caused by these bacteria significantly affect morbidity and mortality, primarily in hospitalized patients. Treatment becomes more expensive, more toxic, and prolonged. This is the reason why research on alternative therapies should be one of the main priorities of medicine and biotechnology. A promising alternative treatment approach is bacteriophage therapy. The effect of the anti-staphylococcal bacteriophage preparation Stafal® on biofilm reduction was assessed on nine S. aureus strains using both sonication with subsequent quantification of surviving cells on the catheter surface and evaluation of biofilm reduction in microtiter plates. It was demonstrated that the bacteriophages destroy planktonic cells very effectively. However, to destroy cells embedded in the biofilm effectively requires a concentration at least ten times higher than that provided by the commercial preparation. The catheter disc method (CDM) allowed easier comparison of the effect on planktonic cells and cells in a biofilm than the microtiter plate (MTP) method.
Keywords: bakteriologické techniky; stafylokokové infekce; stafylokokové bakteriofágy; Colony Count, Microbial; Staphylococcus aureus; mikrobiální viabilita; počet mikrobiálních kolonií; Staphylococcus Phages; Anti-Infective Agents; Microbial Viability; lidé; Methicillin-Resistant Staphylococcus aureus; Biofilms; Humans; Staphylococcal Infections; biofilmy; antiinfekční látky; methicilin rezistentní Staphylococcus aureus; Bacteriological Techniques